The Influence of Teacher Skills in Using ICT Media and Satisfaction with Tutoring Services on Student Motivation in Learning Islamic Education at Junior High Schools in Semarang City - Muhammad Riyas Amir (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
This study examines the impact of educators’ ICT skills and tutoring service satisfaction on student motivation in Islamic Religious Education (PAI) at junior high schools. Using an associative approach, the quantitative research involved 120 students and 20 educators from 20 schools in Semarang City. Data collection included questionnaires, observations, and documentation, while analysis involved descriptive statistics, classical assumption tests, and multiple linear regression. Findings reveal that educators’ ICT proficiency significantly influences student motivation (t-value: 1.782 > t-table: 1.740, significance: 0.04 < 0.05). Tutoring service satisfaction also significantly impacts student motivation (significance: 0.00 < 0.05, t-value: 1.939 > t-table: 1.658). These results highlight the essential role of ICT skills and tutoring satisfaction in enhancing PAI student motivation